Immunohistochemistry of ductal adenocarcinoma of the prostate and adenocarcinomas of non‐prostatic origin: a comparative study. Issue 4 (17th January 2016) - Seipel, Amanda H.; Samaratunga, Hemamali; Delahunt, Brett; Wiklund, Peter; Clements, Mark; Egevad, Lars
Abstract : Ductal adenocarcinoma of the prostate (DAC) has morphological similarities to adenocarcinomas of other organs. DAC behaves in an aggressive manner and may present with metastases. These metastases may occur at unusual sites, which itself may cause diagnostic difficulties. It is important for therapeutic decisions that a prostatic origin of these metastases be established. Our aim was to compare the protein expression of DAC and adenocarcinomas of colon, endometrium, lung, pancreas, stomach and urinary bladder. A tissue microarray was constructed using 60 DAC, 6 colonic, 7 endometrial, 7 lung, 5 pancreatic, 5 gastric, and 9 urinary bladder adenocarcinomas. Slides were stained for estrogen, progesterone and androgen receptor, prolactin, PSA, prostein, PSMA, PSAP, CDX2, lysozyme, villin, monoclonal CEA, CK7, CK20, HMWCK, p63, p504s, c‐Myc, EGFR, Ki‐67, p16, p21, p27, p53, PTEN, ERG, and PAX‐8. Androgen receptor, prostein, PSA, and PSAP were almost invariably expressed in DAC. Ki‐67‐labeling index was lower in DAC than in other adenocarcinomas. The expression patterns of intestinal markers and cytokeratins in DAC were less specific and may lead to diagnostic errors if not combined with prostate‐specific markers.